Corrosion behavior of wire-arc additive manufactured and as-cast Ni-Al bronze in 3.5 wt% NaCl solution. (1st May 2023) - Xu, Cheng; Peng, Yong; Chen, Liang-Yu; Zhang, Tian-Yang; He, Shen; Wang, Ke-Hong
Abstract: The wire-arc additive manufacturing (WAAM) was used to develop Ni-Al bronze (NAB) alloys for naval application. Compared with as-cast NAB, the microstructure of as-fabricated NAB is finer, the precipitation of the κⅠ is suppressed, more uniform distribution of elements, and most β′-phase transformates to α + κⅢ eutectic structures. Additively manufactured sample reveals a lower corrosion current (0.0149 ± 0.0014 mA·cm −2 ) than the counterpart (0.0162 ± 0.004 mA·cm −2 ). After immersion for 30 days, since the film formed on the additively manufactured NAB contains more Al2 O3 and Ni, the mass loss of WAAM-produced NAB alloys decreased by 35.21% compared to the cast samples. Highlights: Nickel-Aluminum Bronze components were fabricated by wire-arc additive manufacturing. Differences in κ-phases formation between WAAM-produced NAB and cast was discussed. WAAM-produced samples showed fine microstructure and uniform element distribution. The more Al2 O3 and Ni in the oxide film formed on the WAAM-produced samples. WAAM-produced NAB exhibited lower corrosion rate and better corrosion resistance.